Examining the Transcriptional Response in Wheat Fhb1 Near‐Isogenic Lines to Fusarium graminearum Infection and Deoxynivalenol Treatment. Issue 1 (1st March 2016) - Hofstad, Anna N.; Nussbaumer, Thomas; Akhunov, Eduard; Shin, Sanghyun; Kugler, Karl G.; Kistler, H. Corby; Mayer, Klaus F.X.; Muehlbauer, Gary J.
Abstract : Fusarium head blight (FHB) is a disease caused predominantly by the fungal pathogen Fusarium graminearum that affects wheat and other small‐grain cereals and can lead to severe yield loss and reduction in grain quality. Trichothecene mycotoxins, such as deoxynivalenol (DON), accumulate during infection and increase pathogen virulence and decrease grain quality. The Fhb1 locus on wheat chromosome 3BS confers Type II resistance to FHB and resistance to the spread of infection on the spike and has been associated with resistance to DON accumulation. To gain a better genetic understanding of the functional role of Fhb1 and resistance or susceptibility to FHB, we examined DON and ergosterol accumulation, FHB resistance, and the whole‐genome transcriptomic response using RNA‐seq in a near‐isogenic line (NIL) pair carrying the resistant and susceptible alleles for Fhb1 during F. graminearum infection and DON treatment. Our results provide a gene expression atlas for the resistant and susceptible wheat– F. graminearum interaction. The DON concentration and transcriptomic results show that the rachis is a key location for conferring Type II resistance. In addition, the wheat transcriptome analysis revealed a set of Fhb1 ‐responsive genes that may play a role in resistance and a set of DON‐responsive genes that may play a role in trichothecene resistance. Transcriptomic results from the pathogen show that the F. graminearum genome responds differently to the host level of resistance. The results of this study extend our understanding of host and pathogen responses in the wheat– F. graminearum interaction.